Three Religious Philosophic Models of Creativity - D. V. Pivovarov (Russian State Vocational Pedagogical University, 2015)
The research paper deals with the concept of creativity and is aimed at demonstrating the paradoxical nature of the creative action. Generally, in modern world, creativity is defined as the «newness creating». However, this is not the only viewpoint, as in different cultures there traditionally compete three generalized definitions of creativity: 1) newness is a recurrence of the old; 2) newness is a unique synthesis of old forms; 3) newness arises from nothing. It has been demonstrated that the above formulas of creativity originate from the three equally strong religious traditions - pantheism, panentheism and monotheism. According to the author, the pantheistic scheme, being applied to human creativity, explains the specificity of scientific theoretical activity. In scientific sphere, as it is well-known, the highest creative achievement is related to discovery (not invention) of fundamental laws of nature dissimilated in a variety of natural phenomena, and predeter- mining them. From the panentheistic model, on the other hand, the secular philosophy deduces the special theory of human creativity, viewed as a free construction and invention, rather then simple discovery of something that already exists. Evidently, the given model appeals to the engineering sphere providing the basis for a number of theories related to inventions and rationalizations. Therefore, the mechanism of inventions is quite simple, and the mass creativity training is possible. Whereas, according to monotheism, creativity is necessarily related to mystery, and therefore, this sort of training is impossible, and the pedagogic technology of creativity is regarded as non- sense. However, such opposing views are quite lawful being proved by the numerous facts of innovations in human history. Using the method of philosophic dialectics, the author achieves a paradoxical synthesis of the above mentioned alternative positions. In author's opinion, the paradox of creativity, stimulating discussions about man's creative dimension, can not be eliminated, and should be taken into account in creativity studies.